2006
DOI: 10.1097/01.mpg.0000226387.56612.1e
|View full text |Cite
|
Sign up to set email alerts
|

Does the Heterozygous State of Alpha‐1 Antitrypsin Deficiency Have a Role in Chronic Liver Diseases? Interim Results of a Large Case‐Control Study

Abstract: We found no association between the heterozygous PiZ state of alpha1ATD and the presence of chronic LD in-general or the presence of cryptogenic cirrhosis. In contrast, patients with decompensated LD of any etiology had a significantly higher prevalence of PiMZ compared with patients with compensated LD. Furthermore, in patients with chronic LD due to HCV or NAFLD there was a significant association between the PiMZ heterozygous state and increased severity of LD and the need for liver transplantation. These i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 20 publications
4
54
1
2
Order By: Relevance
“…Consistently, the minimal liver abnormalities found in both the proband and his mother are probably unrelated to the presence of the defective P brescia α 1 AT allele. These results agree with the presence of only occasional hepatic α 1 AT deposits and the still debated causal association between heterozygous α 1 AT deficiency (PI*M/Z) and chronic liver disease (Fischer, et al, 2000;Regev, et al, 2006). We can suppose that protein polymerization of P brescia α 1 AT could be not sufficient in the heterozygous state to become detectable as liver inclusions.…”
Section: Discussionsupporting
confidence: 80%
“…Consistently, the minimal liver abnormalities found in both the proband and his mother are probably unrelated to the presence of the defective P brescia α 1 AT allele. These results agree with the presence of only occasional hepatic α 1 AT deposits and the still debated causal association between heterozygous α 1 AT deficiency (PI*M/Z) and chronic liver disease (Fischer, et al, 2000;Regev, et al, 2006). We can suppose that protein polymerization of P brescia α 1 AT could be not sufficient in the heterozygous state to become detectable as liver inclusions.…”
Section: Discussionsupporting
confidence: 80%
“…Although these PI mutations were associated with hyperferritinemia and sinusoidal iron accumulation, they were not associated with more severe liver damage in NAFLD ( 270 ). Regev et al showed that, in patients with liver disease, there was a disproportionately higher prevalence of PI *Z among NAFLD patients with decompensated liver disease (5.0%) compared with NAFLD patients with less severe liver disease (1.9%) ( 271 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although homozygous individuals are more likely to develop liver disease, even a single ␣1-ATZ mutation may predispose patients to hepatic injury 3,4,7,32 and act as a modifier gene in the progression of liver disease in patients suffering from cystic fibrosis, 8 non-alcoholic fatty liver disease, and hepatitis C. 5 However, most patients homozygous for the Z mutation never develop clinically relevant liver disease. The development of liver injury in this model therefore must require an environmental or genetic factor in addition to the Z mutation.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Homozygosity for the ␣1-ATZ mutation (also referred to as PiZZ) is generally required for the development of liver disease, although several studies report an increased risk to heterozygous individuals. [3][4][5][6][7] A single ␣1-ATZ mutation may also predispose patients with cystic fibrosis to significant liver disease. 8 Therefore, the ␣1-ATZ mutation not only may cause liver injury but it may act as a modifier gene that exacerbates other forms of liver disease.…”
mentioning
confidence: 99%